Contemporary radiooncological management of bone metastases from breast cancer: factors associated with prescription of different fractionation regimens (short or long course) in a rural part of North Norway with long travel distance - Nieder, Carsten; Dalhaug, Astrid; Haukland, Ellinor; Mannsåker, Bård; Pawinski, Adam (International Journal of Circumpolar Health, 2017)
Source at https://doi.org/10.1080/22423982.2016.1270080 . The aim of this study was to reduce barriers that prevent implementation of evidence-based recommendations about single-fraction palliative radiotherapy (PRT) and to demonstrate that single-fraction PRT yields similar outcomes as long-course treatment (≥10 fractions) in patients with bone metastases from breast cancer. This retrospective study (2007–2014) included 118 Norwegian female patients. All patients received guideline-conform systemic therapy including bone-targeting agents. Median survival was 12.7 months. Long-course PRT was prescribed in 60% of patients, while 21% had PRT with a single fraction of 8 Gy to at least one target. Reirradiation rate was not significantly higher after 8 Gy (9%, compared to 5% after long-course PRT and 6% after 4 Gy x5). Patients with favorable baseline characteristics such as younger age and good performance status (PS) were significantly more likely to receive long-course PRT. Biological subtype and comorbidity did not correlate with fractionation. Prognosis was influenced by biological subtype, extra-skeletal disease extent, severe anemia and abnormal CRP. The limited need for reirradiation after single fraction PRT might encourage physicians to prescribe this convenient regimen, which would improve resource utilization. Even patients with PS3 had a median survival of 3 months, which indicates that they could experience worthwhile clinical benefit.